COVID-19 LOCKDOWN AND STUDENTS’ PERCEPTION OF ONLINE LEARNING INITIATIVE IN AL-HIKMAH UNIVERSITY, NIGERIA: IMPLICATIONS FOR MANAGEMENT - Suleiman , Yusuf; Adam Ishola , Mustapha; Nusirat Omofolakemi, Oniyeye; Olamide Jemeelah, Olajide; Sekinat Atinuke , Katibi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2022)
The global covid-19 pandemic forced higher institutions in Nigeria to migrate from traditional mode of teaching to online platform. It is on this premise that this study examined covid-19 lockdown and students’ perception of online learning Initiative in Al-Hikmah University, Nigeria. Research design of descriptive type was adopted for the study. Four research questions were formulated for the study. The population consists of all 9,426 students in Al-Hikmah University. Stratified and random sampling techniques were used to select 375 respondents across all 7 faculties in the university. An instrument titled ‘Students’ Perception of Online Learning Initiative Questionnaire (SPOLIQ)’’ was adapted to elicit relevant data via google form. The data collected were analysed using descriptive method. Findings revealed that online learning initiative was very helpful to students amidst lockdown. Specifically, students enjoyed the use of whatsapp, zoom and telegram as platforms for receiving lectures. Findings indicate that some challenges were associated with the use of online leaning. They include inadequate data subscription and network problem among others. Lastly, adequate data subscription and good internet service were suggested as measures that can be used to improve online learning in the university.